2018
DOI: 10.1124/mol.117.110445
|View full text |Cite
|
Sign up to set email alerts
|

Concentrative Transport of Antifolates Mediated by the Proton-Coupled Folate Transporter (SLC46A1); Augmentation by a HEPES Buffer

Abstract: The proton-coupled folate transporter (PCFT) is ubiquitously expressed in solid tumors to which it delivers antifolates, particularly pemetrexed, into cancer cells. Studies of PCFT-mediated transport, to date, have focused exclusively on the influx of folates and antifolates. This article addresses the impact of PCFT on concentrative transport, critical to the formation of the active polyglutamate congeners, and at pH levels relevant to the tumor microenvironment. An HeLa-derived cell line was employed, in whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…PCFT has recently emerged as a predictive parameter in MPM patients treated with pemetrexed-based chemotherapeutic regimens, since low PCFT expression was associated with shorter PFS and OS. 13 PCFT is the main transporter mediating pemetrexed influx, with remarkable transport Km values of 0.2–0.8 μM at acidic pH, 42 and its expression has been linked to growth-inhibitory activity of pemetrexed after transfection into a folate transporter-null cell variant. 43 We consistently observed that PCFT silencing increased the IC 50 values of pemetrexed in our MPM cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…PCFT has recently emerged as a predictive parameter in MPM patients treated with pemetrexed-based chemotherapeutic regimens, since low PCFT expression was associated with shorter PFS and OS. 13 PCFT is the main transporter mediating pemetrexed influx, with remarkable transport Km values of 0.2–0.8 μM at acidic pH, 42 and its expression has been linked to growth-inhibitory activity of pemetrexed after transfection into a folate transporter-null cell variant. 43 We consistently observed that PCFT silencing increased the IC 50 values of pemetrexed in our MPM cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms of this transporter have been associated with an increase in adverse drug responses [228,229]. SLC46A1 provides an intriguing opportunity to harness its concentrative transport activity in acidic environments, which are often found in the tumor microenvironment [230]. SLC46A1, which is ubiquitously expressed in solid tumors, could in principle afford a more targeted delivery of antifolate drugs to tumor cells [230].…”
Section: Vitamin Transporters In Cancermentioning
confidence: 99%
“…SLC46A1 provides an intriguing opportunity to harness its concentrative transport activity in acidic environments, which are often found in the tumor microenvironment [230]. SLC46A1, which is ubiquitously expressed in solid tumors, could in principle afford a more targeted delivery of antifolate drugs to tumor cells [230]. Expression of SLC19A3 in cancerous cells has been shown to be both increased and decreased and further studies are needed to elucidate the role SLC19A3 plays in cancer cells [224,231].…”
Section: Vitamin Transporters In Cancermentioning
confidence: 99%
“…Losing the function of the proton-coupled folate transporter protein caused hereditary folate malabsorption ( 49 ). In addition, SLC46A1 transports folic acid, methotrexate, and pemetrexed ( 34 36 ). The lysosomal copper transporter SLC46A3 was localized to the lysosome, modulating intracellular copper levels ( 26 ).…”
Section: Discussionmentioning
confidence: 99%